The Influence of organizational culture on the quality of education - Herayati Herayati (Institute of Computer Science (IOCS), 2023)
Culture is the foundation for the formation of an organization, because organizational culture is the identity of an organization. There are several opinions about the notion of organizational culture, the most popular opinion is that organizational culture is the subject of solving external and internal problems. It is understood that an organization is established to solve a problem. An education usually has an organization. Organizations in education have Organizational roles that can help support the quality of education. Organization is an important component in life, especially in the sphere of education. Therefore, it is worth being grateful for the existence of an organization in life. Without organization, perhaps mankind will find it difficult to solve a problem. This study aims to find out and explain the influence of organizational culture on educational quality. The method used in this study is a quantitative descriptive method, the sample used was obtained from 40 students from various study programs and universities located in the provinces of Banten, DKI Jakarta, and West Java which were taken randomly through friendship contacts from the researcher's Whatsapp application. The data collection technique used is an interview. The results showed that organizational culture is very influential and important to the quality of education. This is indicated by the high percentage reaching 100%. And also by joining the organization will have a good impact on academic scores, it is shown that 75% of students respond well, 7.5% have a bad impact, 17.5% have no impact. The opinion of 40 students said that the influence of organizational culture is very important and influential and has a good impact on the Quality of Education.